2002
DOI: 10.1016/s0005-2736(01)00443-6
|View full text |Cite
|
Sign up to set email alerts
|

Conformational mapping of the N-terminal peptide of HIV-1 gp41 in membrane environments using 13C-enhanced Fourier transform infrared spectroscopy

Abstract: The N-terminal domain of HIV-1 glycoprotein 41000 (FP; residues 1--23; AVGIGALFLGFLGAAGSTMGARSCONH(2)) participates in fusion processes underlying virus--cell infection. Here, we use physical techniques to study the secondary conformation of synthetic FP in aqueous, structure-promoting, lipid and biomembrane environments. Circular dichroism and conventional, (12)C-Fourier transform infrared (FTIR) spectroscopy indicated the following alpha-helical levels for FP in 1-palmitoyl-2-oleoylphosphatidylglycerol (POPG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
136
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(152 citation statements)
references
References 102 publications
13
136
2
Order By: Relevance
“…Infrared structural investigations of membrane-associated HFP have generally been consistent with predominant antiparallel β-sheet conformation and were based on analysis of the wavenumbers of the amide I transition. 17,51,81,82 One infrared study proposed that there was β-hairpin structure in the Ala-1 to Gly-16 region but the present work did not support this model because there were no residues in this region with non-β-strand 13 C shifts. 51 To our knowledge, the complete 13 C shift assignment of the present study is the first definitive evidence for a fully extended conformation.…”
Section: Discussioncontrasting
confidence: 85%
“…Infrared structural investigations of membrane-associated HFP have generally been consistent with predominant antiparallel β-sheet conformation and were based on analysis of the wavenumbers of the amide I transition. 17,51,81,82 One infrared study proposed that there was β-hairpin structure in the Ala-1 to Gly-16 region but the present work did not support this model because there were no residues in this region with non-β-strand 13 C shifts. 51 To our knowledge, the complete 13 C shift assignment of the present study is the first definitive evidence for a fully extended conformation.…”
Section: Discussioncontrasting
confidence: 85%
“…This result correlated with previous studies which supported the following structural features: (1) β strand HFP was fully extended between A1 and G16; (2) β strand HFP formed hydrogen bonded oligomers or aggregates; and (3) a significant fraction of the oligomers have an antiparallel arrangement with adjacent strand crossing between F8 and L9 (25,(27)(28)(29)35,37,85,86). Some of these studies also supported conformational disorder at A21 (27,28).…”
Section: Insertion Modelssupporting
confidence: 89%
“…It has therefore been hypothesized that during viral/target cell fusion, at least three HFPs insert into the target cell membrane with their C-termini in close proximity. There is some antibodybased evidence for this hypothesis (21).A variety of experimental methods have shown that membrane-associated HFP can assume either helical or nonhelical structure (5,7,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Models for the helical structure have been developed based on nuclear magnetic resonance (NMR), electron spin resonance (ESR), infrared (IR), and circular dichroism (CD) data, as well as computer simulations (33)(34)(35)(36)(37)(38)(39).…”
mentioning
confidence: 99%